(untitled) (Journal of Technology and Operations Management, 2017)
The Malaysian government has been striving to provide an environment conducive to research commercialisation in the country. Despite the efforts, the targeted research commercialisation rate has yet to be achieved. This paper explores the motivation of the academic researchers who had successfully commercialised their research. Literature classifies motivation factors as extrinsic, intrinsic, and prosocial, which might exist independently or in a combination (mixed-motivation). Within the academic research commercialisation context, a considerable number of existing studies have discussed the role of extrinsic motivation factors, while the issues of intrinsic and prosocial factors have not been much studied. Thus, this study proposed a conceptual framework to further understand the role of each motivation factor as well as the role of mixed-motivation factors among academic researchers who had successfully commercialised their research results. Finally, this research enriches the dearth of research commercialisation literature in Malaysian university settings.